Treinamento dos músculos do assoalho pélvico associado ou não ao método Pilates para o tratamento da incontinência urinária de esforço feminina: ensaio clínico randomizado - Borges, Fernanda Araújo (2018)
Objective: To evaluate the effect of adding the Pilates method to a pelvic floor muscle training program for the treatment of female stress urinary incontinence. Method: A randomized controlled clinical trial that included women complaining of urine leakage to efforts, sedentary and who had never had contact with pelvic floor muscle training. Forty-three volunteers randomized into two groups: Group P + PFMT (n = 23) and TMAP group (n = 20). The P + PFMT group underwent a Pilates exercise regimen with verbal command for voluntary contraction of the pelvic floor muscles and the PFMT group underwent a traditional pelvic floor muscle training program. The impact of the symptoms on the woman's life and the function of the pelvic floor muscles (PFM) were considered as primary and secondary outcome, respectively. The impact of the symptoms was evaluated by the questionnaires PFDI-SF-20 and ICIQ-SF. MAP function was assessed by vaginal palpation, quantified by modified Oxford scale and contraction pressure assessed by manometry. The treatment protocol for both groups was performed for six weeks, totaling 12 sessions of approximately 50 minutes each with progressive overload. Results: The impact of urinary symptoms was improved through the ICIQ-SF (p <0.000) and PFDI-20 (p <0.000) questionnaires and increased PFM strength assessed by peak manometry (p = 0.036) and Oxford (<0.000) in both groups at the end of treatment. Conclusion: Adding Pilates to a TMAP program was not superior to TMAP alone for the treatment of female SUI and TMAP should continue as the first treatment option for this disorder.